Evil in mind: the psychology of harming others - Burris, Christopher T. (Oxford University Press, 2022)
What is "evil" -- "Evildoers" : who (or what) earns the title? -- The "mark of Cain" -- Becoming evil -- Hate -- Sadism -- Serial killers -- Organized evil -- "Evil" spelled backwards is...?.